Errors of Spelling, Capitalization, and Punctuation Marks in Writing Encountered by First Year College Students in Al-Merghib University Libya - A Shweba, Abdusalam Alhadi; Mujiyanto, Yan (English Education Journal, 2017)
Writing as the productive skill is considered to be more difficult than any other productive skill. Students face difficulties and commit errors in many different writing skills, especially in mechanics (punctuation, capitalization, and spelling).The study examined the errors of writing skill that face first year English college students of Al-Merghib University in related to the three mechanics. There were thirty participants of different genders in the study. They were thirteen males and seventeen females who studies in the first year of English college in Al-Meghib University. To achieve the objectives of the study, qualitative design was employed. The data was collected using two methods: 1) questionnaire to check the participants' knowledge about the punctuation, capitalization, and spelling usage and 2) a test to analyze these errors in the respondents' written language. To analyze the data, simple statistics description was used. The result of the study found that capitalization error was the most committed one, followed by the punctuation error, and spelling error was the least error committed by the first year English college students. It was concluded that most of the respondents committed some errors because of their lack of knowledge, lack of balance in the curriculum and the influence of mother tongue. Writing classes must engage students with more practices than ask them to deliver lectures. Also, this study provides some helpful suggestions to avoid the identified errors. The study can be used as an insight to the next other researchers and as a reference for similar topics about writing skills. Teachers must pay deep attention to the use of all the punctuation marks, explain the conventions of capitalization, and clarify more about the spelling rules. Students should be encouraged to do home written assignments as much as possible.